Trait emotional intelligence is related to risk taking when adolescents make deliberative decisions - Angelo Panno (Games, 2016)
Most forms of risky behavior reach their peak during adolescence. A prominent line of research is exploring the relationship between people's emotional self-efficacy and risk taking, but little is known about this relationship in the cognitive-deliberative domain among adolescents. The main aim of the present study consists in investigating whether trait EI (Emotional Intelligence) is positively related to risk taking under predominantly cognitive-deliberative conditions among adolescents. Ninety-four adolescents played the cold version of the Columbia Card Task one month following an assessment of their trait EI. Results showed that trait EI is associated with risk taking under cognitive-deliberative conditions among adolescents. Moreover, the present research showed that trait EI is related to risk taking through the decision makers' self-motivation. These results provide novel insights into research investigating the connections between emotional intelligence, decision science and adolescence research.
Keywords: 330; emotional intelligence; risk taking; decision making; adolescence; emotion